Managing organizational change a multiple perspectives approach - Palmer, Ian 1957-; Dunford, Richard; Akin, Gib (Mc-Graw Hill Education, 2009)
Provides managers with an awareness of the issues involved in managing change, moving them beyond "one-best way" approaches and providing them with access to multiple perspectives that they can draw upon in order to enhance their success in producing organizational change